2006
DOI: 10.1002/uog.2828
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative sum (CUSUM) analysis in the assessment of trainee competence in fetal biometry measurement

Abstract: Objective To determine the value of cumulative sum (CUSUM) analysis in assessing trainee proficiency in fetal biometry measurement. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Weerasinghe et al studied three trainees who learned ultrasonic fetal biometry measurements. 11 Each trainee studied 100 patients. They found that 13 to 30 cases were required to measure fetal biparietal diameter at the 90% level of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Weerasinghe et al studied three trainees who learned ultrasonic fetal biometry measurements. 11 Each trainee studied 100 patients. They found that 13 to 30 cases were required to measure fetal biparietal diameter at the 90% level of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical medicine the need for quality control arose [21,22] , but only in the early 1990s several medical studies used CUSUM analysis to monitor operators' performance and to describe learning curves [23,24] . Nowadays, CUSUM analysis is increasingly used for various clinical procedures [25][26][27][28] . Risk-adjusted CUSUM has the advantage to take into account variations in pre-procedure or pre-operative risks [29] , but these must be identifiable and clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…That means that for each failure, the line will go up by 0.78 and for each success it will go down by 0.22 declaring competence when the plot falls below the lower boundary of h1, i.e. dropping below 2 consecutive boundary lines [15]. …”
Section: Methodsmentioning
confidence: 99%
“…CUSUM analysis was obtained for each intrapulmonary artery Doppler parameter according to elsewhere-published standard methodology [12,13,14,15,16,23,24,25] and using Excel for Windows 2010 (Microsoft Corp., Redmond, Wash., USA) statistical software. In brief, the CUSUM values are plotted on the y-axis and the number of examinations on the x-axis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation